SAFEHAVEN ATAU RISKY HAZARD? PASAR SAHAM INDONESIA VS EMAS, BITCOIN, DAN US DOLLAR MENGGUNAKAN METODE VECTOR AUTOREGRESSION (VAR) (Data Harian IHSG, Emas, Bitcoin, dan Dollar Amerika Periode Desember 2016 – Desember 2021) - Arief Setyo Wicaksono; Erman Denny Arfianto (Faculty of Economics and Business Diponegoro University, 2022)
This study aims to analyze the role of JCI, Gold, Bitcoin, and the US Dollar. The data used in this study is daily data on JCI returns, Gold returns, Bitcoin returns, and US Dollar returns for 5 years starting on 8 December 2016 to 08 December 2021, all of the data used has been converted into Rupiah currency units. The data was then analyzed using the Vector Auto Regression (VAR) model. The findings from this study show that the JCI response to changes in the prices of Gold, Bitcoin, and the US Dollar shows the JCI moves positively, Gold responds negatively to shocks caused by the JCI and Bitcoin, Gold responds positively to shocks in the US Dollar, Bitcoin does not respond to shocks. caused by the JCI, Gold, and the US Dollar, and the US Dollar responded negatively to the shocks caused by the JCI, Gold, and Bitcoin. These results show that Gold and the US Dollar are able to become safe-haven assets and the US Dollar is a better safe-haven asset than Gold, while JCI and Bitcoin are only capable of being risky hazard assets.